Analisis Penyebab Rendahnya Kepatuhan Konsumsi Tablet Fe pada Remaja Putri di Daerah Pesisir Kecamatan Kabaena Timur - Zamadi, Zamadi; Desa, Desiderius Bela; Muhim, Habib Ihsan (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Teenage girls are prone to anemia so they need Fe tablets to prevent anemia, but teenagers are not obedient in taking Fe tablets. This study aims to determine the factors that cause stunting in toddlers in the coastal area of ​​Sorue Jaya Village, Soropia District, Konawe Regency. This research is a quantitative research with a cross sectional study design. The population is all young women in the coastal area of ​​East Kabaena in 2020 as many as 1,382 people and a sample of 91 people obtained by proportional stratified random sampling. Data on compliance with Fe tablet consumption, the effect of consuming Fe tablets, knowledge, roles of health workers and family support were obtained by distributing questionnaires. Data were analyzed using chi-square test. The results showed that of the 92 samples, most were non-adherent (60.2%), then most (67.7%) experienced the effects of consuming Fe tablets. Furthermore, most of the sample knowledge (57.0%) is sufficient. The role of health workers (62.4%) is mostly lacking and family support (71.0%) is mostly unsupportive. The results of the chi-square test obtained a p value of 0.000 for the variables of the relationship between the effect of Fe tablet consumption, knowledge and family support with adherence to Fe tablet consumption and p value 0.008 <0.05 for the relationship between the role of health workers and adherence to Fe tablet consumption. The conclusion of this study is the effect of consuming Fe tablets, knowledge, the role of health workers and family support are the causes of low adherence to Fe tablet consumption in adolescent girls in the coastal area of ​​East Kabaena District.